Women’s Participation in Middle Eastern Politics: Between Cultural Norms and Democratic Aspirations - Abidi, Siham; Marah, Thomas Sheku (Journal Of Middle East and Islamic Studies, 2026)
Women’s political participation in the Middle East remains shaped by the complex interaction of cultural norms, religious interpretations, and democratic reform processes. While existing scholarship has examined these factors extensively, limited attention has been devoted to explaining why women’s political participation varies across states with broadly similar socio-cultural and religious contexts. This study addresses this gap through a qualitative comparative analysis of Tunisia, Saudi Arabia, and Iran. Guided by Feminist Institutionalism and Political Opportunity Structure theory, the study draws on secondary data from peer-reviewed literature, legal documents, and policy reports. The findings demonstrate that women’s political participation is not determined by culture or religion alone but by the interaction between informal gender norms and institutional opportunity structures. Tunisia achieved comparatively higher levels of political inclusion through democratic opening and constitutional reform, whereas Saudi Arabia experienced controlled participation through state-led modernization. In Iran, restrictive institutions redirected political engagement toward grassroots activism. The study contributes to debates on gender, Islamic politics, and democratization in the Middle East.